2014
DOI: 10.1155/2014/785752
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Interventions and Protective Thresholds to Prevent Disease Transmission in Deploying Populations

Abstract: Military personnel are deployed abroad for missions ranging from humanitarian relief efforts to combat actions; delay or interruption in these activities due to disease transmission can cause operational disruptions, significant economic loss, and stressed or exceeded military medical resources. Deployed troops function in environments favorable to the rapid and efficient transmission of many viruses particularly when levels of protection are suboptimal. When immunity among deployed military populations is low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…One model of a hypothetical outbreak in South Africa assumed that measles treatment impacts transmission (without providing any support for this assumption, which appears inconsistent with other models and the evidence), and suggested that saturation of treatment may support sustained transmission. Based on current rates of immunization among U.S. troops, a recent study found limited benefit associated with predeployment boosting immunization with MRCV for troops going to Afghanistan, although the model did not explicitly consider the impact of individual importations that could lead to limited local transmission and associated costs …”
Section: Resultsmentioning
confidence: 99%
“…One model of a hypothetical outbreak in South Africa assumed that measles treatment impacts transmission (without providing any support for this assumption, which appears inconsistent with other models and the evidence), and suggested that saturation of treatment may support sustained transmission. Based on current rates of immunization among U.S. troops, a recent study found limited benefit associated with predeployment boosting immunization with MRCV for troops going to Afghanistan, although the model did not explicitly consider the impact of individual importations that could lead to limited local transmission and associated costs …”
Section: Resultsmentioning
confidence: 99%
“…The military population structure for this study was built upon previous analyses [ 23 ]. The simulated deployed population consisted of 4 subpopulations defined by interaction with the local population, ranging from negligible to high levels of daily contact.…”
Section: Methodsmentioning
confidence: 99%
“…In- and outbound rotation rates ( b IN and b OUT ) varied over the 10-year period to allow for force increase and decrease (see Figure 1 ) and a daily casualty rate ( μ ) accounted for removal of individuals for reasons other than rotation or polio-related disease. See Burgess et al [ 23 ] for additional population details.…”
Section: Methodsmentioning
confidence: 99%